Formulation of Faḍīlah, Ikhtiyār, and Jawāz Times of Asr Prayer of Fiqh and Science Perspectives - Diana Manzil, Li'izza; Amalia, Ridha (KnE Social Sciences, 2024)
Asr prayer is one of the obligatory prayers performed at specific times among the five daily prayers. However, in the literature of fiqh, there is a division of Salat Asar into faḍīlah (preferred time), ikhtiyār (permissible time), and jawāz (allowable time). This is closely related to the virtue of performing the prayer in its early time, as mentioned in the sayings of the Prophet Muhammad, and the discouragement of delaying Asr prayer until its later time. It is essential to establish a precise time, specifying the exact hour and minute for faḍīlah, ikhtiyār, and jawāz in Asr prayer. There are two methods for determining the timing of faḍīlah, ikhtiyār, and jawāz: firstly, through a fiqh approach, which involves observing the phenomena of the Sun’s movement, and secondly, through a scientific approach, using mathematical and astronomical calculations. Both the fiqh and scientific methods are integrated and mutually beneficial in the development of a formulation, providing ease in determining the timing of faḍīlah, ikhtiyār, and jawāz in Salat Asar. Keywords: Asr prayer, Faḍīlah, Ikhtiyār, Jawāz, fiqh, science